Rainwater unable to quench the thirst, now hopes from dew drops - Machiwal, Deepesh; Kumar, Sanjay; Dayal, Devi (Indian Farming, 2018)
Quantities of dew water are definitely negligible in comparison to that collected through rainfall, and perhaps, this is the major cause that many people in India still guess that dew has no importance for human use. However, in the western part of the country, where rainwater quantities are incapable to meet the drinking water needs entirely, hopes are now from the dew drops.